Analysis of carrier trapping and emission in AlGaN/GaN HEMT with bias‐controllable field plate. Issue 8 (16th June 2017) - Mase, Suguru; Wakejima, Akio; Egawa, Takashi
Abstract : We analyzed carrier trapping in AlGaN/GaN HEMT occurring between gate and drain with a bias‐controllable Field Plate (CFP) on a Si3 N4 passivation, which is structurally and electrically independent from other electrodes. We observed the recovery of a transient drain current which was associated with carrier emission after the momentary pulse bias of CFP. From the temperature dependence of pulsed I–V measurements, an activation energy of the trap state was 0.083 eV and capture cross section was 2.0 × 10 −24  cm −2 . This value is the same to the activation energy of the surface leakage current in AlGaN/GaN HEMT with Si3 N4 passivation. The trap state with the activation energy of 0.083 eV has important role in pulse operation of AlGaN/GaN FP‐HEMT with Si3 N4 passivation.